2014
DOI: 10.1213/xaa.0000000000000098
|View full text |Cite
|
Sign up to set email alerts
|

Awake Microlaryngoscopy and Serial Balloon Dilation in a Third Trimester Multigravida with Subglottic Tracheal Stenosis

Abstract: Tracheal stenosis in pregnancy is a relatively rare occurrence and there are limited data regarding the perioperative management of these patients. Various surgical treatment options are available to include open repair, long-term tracheostomy, or endoscopic repair (rigid versus balloon dilation). We report the case of a woman in her third trimester of pregnancy, with known recurrent and worsening history of subglottic tracheal stenosis, who underwent awake microlaryngoscopy with potassium titanyl phosphate la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…Management of subglottic stenosis in pregnancy has only rarely been reported in the literature, and is limited to a small number of case reports (Table 2). 12 26 Management options have included no intervention, intubation, dilation under inhalational anaesthesia, dilation using topical anaesthesia with or without intravenous sedation, and tracheostomy. In one case, the patient expired several weeks after delivery from subsequent airway obstruction 14 .…”
Section: Discussionmentioning
confidence: 99%
“…Management of subglottic stenosis in pregnancy has only rarely been reported in the literature, and is limited to a small number of case reports (Table 2). 12 26 Management options have included no intervention, intubation, dilation under inhalational anaesthesia, dilation using topical anaesthesia with or without intravenous sedation, and tracheostomy. In one case, the patient expired several weeks after delivery from subsequent airway obstruction 14 .…”
Section: Discussionmentioning
confidence: 99%
“…One of these cases was managed under LA and sedation while the other had GA. 10 A combination of radial incisions into the stenotic segment with potassium titanyl phosphate laser and balloon dilatation has also been described in the third trimester of pregnancy. 11,12 Successful use of carbon dioxide laser and balloon dilatation under GA in the last trimester has been reported with excellent results. 8,14 Our preference is to use endoscopic balloon dilatation with steroids and laser as adjuncts, a technique we have used extensively in the non-pregnant patient with iSGS.…”
Section: Discussionmentioning
confidence: 99%
“…Reported airway management approaches of iSGS in pregnancy range from surveillance, endoscopic surgery and tracheostomy. [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] Endoscopic interventions are the predominant surgical technique reported in the literature, [7][8][9][10][11][12][13][14][15][16][17] but some authors espouse the benefit of a surgical tracheostomy. 18,19 The aim of the study is to describe the use of endoscopic balloon dilation with laser and jet ventilation in the management of iSGS in pregnancy and provide an overview of the current literature.…”
Section: Introductionmentioning
confidence: 99%
“…Instead, more reassuring may be the absence of aspirations in more than 5000 general anesthetics for cesarean deliveries in the Society for Obstetric Anesthesia and Perinatology (SOAP) serious complications registry. 11 The combination of these studies and considering that tubeless open airway surgery has been performed under general anesthesia using nasal oxygen, jet ventilation and THRIVE [3][4][5][6]12,13 in numerous publications, we concluded that it would be relatively safe to fulfill the surgeon's request for an open airway. Still acknowledging the potential risk, we remained on standby for a rapid intubation using a microlaryngoscopy tube size 4.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, managing a pregnant woman for a procedure in their airway under a general anesthesia without a secure airway is a rare occurrence. 8,12,13 Beyond, the original STRIVE Hi study group 8 that included a woman at 23 weeks of gestation in their cohort, there are only 2 other case reports to date describing a spontaneous breathing technique in parturients. First was a women at 29 weeks of gestation who received insufflated oxygen via a nasal airway, while receiving total intravenous anesthesia using propofol and remifentanil, without a described protocol.…”
Section: Discussionmentioning
confidence: 99%